Mode of delivery and fetal outcome in meconium stained amniotic fluid in DMCH - Nesa, Fazilatun; Chowdhury, Fahmida; Yasmeen, BH Nazma; Rahman, Shabnam; Begum, Nasreen; Hossain, SK Akbar (Northern International Medical College Journal, 2018)
Background : Meconium is a dark greenish mass of desquamated cells, mucus, and bile that accumulates in the bowel of a fetus and is typically discharged shortly after birth. Meconium stained amniotic fluid (MSAF) has long been considered to be a bad predictor of fetal outcome. Objective : The aim of this study was to determine if the perinatal outcome is affected by mode of delivery in meconium-stained amniotic fluid. Methodology : This ovservational study was carried out in the department of Obstetrics and Gynaecology in Dhaka Medical College Hospital from July 2016 to June 2017. A total of 204 women who satisfied the inclusion and exclusion criteria were taken for the study. The study group comprised of 102 women admitted in labour and having meconium stained amniotic fluid and 102 women in labour but having clear amniotic fluid were taken as comparision group. Results : The mean age was found 26.6±5.9 years in MSAF group and 26.2±5.0 years in clear liquor group. The mean gestational age was found 38.9±1.8 weeks in MSAF group and 38.5±1.3 weeks in clear liquor group. Risk factors were not statistically significant (p>0.05) between two groups. Forty-one (40.2%) patients had caesarian section in MSAF group and 19(18.6%) in clear liquor group. APGAR score at 1 minute and at 5 minute were statistically significant (p<0.05) between two groups. About 100(98.0%) babies were alive in MSAF group and 101(99.0%) in clear liquor group. Conclusion : Meconium stained amniotic fluid group was associated with higher rate of cesarean delivery, increased need for neonatal resuscitation, increased rate of PIH, pre-eclamsia, Oligohydramnios, IUGR, Post dated pregnancy, Rh incompatibility, GDM and long time hospital stay and hospital mortality. Northern International Medical College Journal Vol.9(2) Jan 2018: 304-307